Hollow mesoporous silica nano-material as well as preparation method and application thereof

By using hollow mesoporous silica nanomaterials as carriers, the problems of low bioavailability and oxidation of astaxanthin are solved, and its efficient utilization and stability are improved in aquatic animals.

CN119637889APending Publication Date: 2025-03-18SHANGHAI OCEAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510053546.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Astaxanthin has low bioavailability and is prone to oxidation, and lacks effective delivery carriers and pathways, making it difficult to improve its utilization rate.

Method used

The hollow mesoporous silica nanomaterial is used as a carrier and prepared by the sol-gel method to form a nanomaterial with a large specific surface area and an internal cavity, which can payload and protect astaxanthin.

Benefits of technology

It improves the utilization rate and stability of astaxanthin, making it easier to be absorbed by spinnaker clams after feeding, significantly improving the color of the clam shell and pearls.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005240679880000011
    Figure HDA0005240679880000011
  • Figure HDA0005240679880000012
    Figure HDA0005240679880000012
  • Figure HDA0005240679880000013
    Figure HDA0005240679880000013
Patent Text Reader

Abstract

The invention provides a hollow mesoporous silica nano-material as well as a preparation method and application thereof, and belongs to the field of nano-carrier preparation. The preparation method comprises the following steps: preparing solid meso-porous silicon spheres by adopting a sol-gel method, forming an ethanol-ammonia water-water mixed system by taking CTAB (Cetyltrimethyl Ammonium Bromide) as a template agent, ammonia water as a catalyst and ethanol and water as solvents, catalyzing tetraethoxysilane to decompose by ammonia water in the mixed system, and forming the solid meso-porous silicon spheres through the template agent; the preparation method comprises the following steps: preparing solid mesoporous silicon spheres, then spontaneously converting the solid mesoporous silicon spheres into hollow mesoporous silicon spheres through a condensation reaction, then removing a template agent, and finally optimizing the structures of the hollow mesoporous silicon spheres through heat treatment, so that the obtained hollow mesoporous silicon dioxide nano material HMSS has the characteristics of large specific surface area, low density and adjustable internal cavity size. Meanwhile, mesopores in the silicon dioxide shell layer provide a large substance inlet and outlet channel, the thickness of the silicon dioxide shell layer is adjustable, and the surface can be modified.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nano-carrier preparation, and in particular to a hollow mesoporous silica nano-material and a preparation method and application thereof. Background Art

[0002] The main pigment in aquatic animals is carotenoids, and astaxanthin (ASX) is the final product of the carotenoid synthesis process. Once it enters the animal body, astaxanthin can be directly deposited into the tissue without any change or biochemical modification. It has a strong pigment deposition function, making the skin and muscles of some aquatic animals appear healthy and bright, and can also make the feathers and skin of poultry appear healthy golden or red. Astaxanthin is a typical keto-carotenoid compound, with a chemical name of 3,3'-dihydroxy-4,4'-diketo-β,β'-carotene and a chemical formula of C 40 H 52 O4, with a relative molecular mass of 596.86, has a chemical structure composed of four isoprene units connected by conjugated double bonds, and each end is formed by two isoprene units to form a unique six-membered ring structure. As a biological additive to improve the body color of aquatic animals, astaxanthin has been vigorously developed in improving the body color of fish, shrimp, and crabs, and there have also been a few studies on the color improvement of the pearls of the triangular oyster. Pearl is a precious organic gem produced by shellfish, and its color is an important factor affecting the development of the pearl industry. However, the uniqueness of the astaxanthin molecular structure lies in the fact that it contains conjugated double bond chains. These conjugated double bond chains and their final unsaturated ketone groups, as well as the presence of hydroxyl groups, make it more susceptible to factors such as light irradiation, temperature changes, and oxidants, resulting in changes in the molecular structure and ultimately degradation into astaxanthin, resulting in low bioavailability of astaxanthin and being easily oxidized. At present, astaxanthin lacks effective delivery carriers and pathways, and there is no clear statement on the mechanism of direct coloring of astaxanthin, which makes it difficult to improve the utilization rate of astaxanthin.

[0003] Therefore, providing a carrier that can effectively load astaxanthin, thereby improving the utilization rate of astaxanthin, has become a technical problem that needs to be urgently solved in the field. Summary of the invention

[0004] The purpose of the present invention is to provide a hollow mesoporous silica nanomaterial and a preparation method and application thereof. The hollow mesoporous silica nanomaterial prepared by the preparation method provided by the present invention can load astaxanthin well, so that it has a higher utilization rate after feeding.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a hollow mesoporous silica nanomaterial, comprising the following steps:

[0007] (1) mixing CTAB, tetraethyl orthosilicate, ammonia water, ethanol and water and performing a hydrolysis reaction to obtain a gel-like mixture;

[0008] (2) mixing the gel mixture obtained in step (1) with water to carry out a condensation reaction, and then adding hydrochloric acid to remove the template to obtain hollow mesoporous silica spheres;

[0009] (3) heat-treating the hollow mesoporous silicon spheres obtained in step (2) to obtain hollow mesoporous silica nanomaterials.

[0010] Preferably, in step (1), the ratio of the mass of CTAB, the volume of tetraethyl orthosilicate, the volume of aqueous ammonia, the volume of ethanol and the volume of water is (0.1-0.5) g: (1-3) mL: (0.1-1) mL: (40-50) mL: 100 mL.

[0011] Preferably, the temperature of the hydrolysis reaction in step (1) is 30 to 40° C., and the time of the hydrolysis reaction is 20 to 30 hours.

[0012] Preferably, the temperature of the condensation reaction in step (2) is 50 to 80° C., and the time of the condensation reaction is 1 to 3 hours.

[0013] Preferably, the temperature of the de-template treatment in step (2) is 50-80° C., and the time of the de-template treatment is 10-15 hours.

[0014] Preferably, the heat treatment temperature in step (3) is 500-600° C., and the heat treatment time is 4-10 h.

[0015] Preferably, the specific surface area of ​​the hollow mesoporous silica nanomaterial in step (3) is 800 to 900 m 2 / g, the average pore size of the hollow mesoporous silica nanomaterial is 2 to 50 nm.

[0016] The present invention provides a hollow mesoporous silica nanomaterial prepared by the preparation method described in the above technical solution.

[0017] The present invention provides the use of the hollow mesoporous silica nanomaterial described in the above technical solution in loading astaxanthin.

[0018] Preferably, the application comprises the following steps:

[0019] 1) mixing astaxanthin and acetone to obtain an astaxanthin buffer solution;

[0020] 2) The astaxanthin buffer solution obtained in step 1) is mixed with the hollow mesoporous silica nanomaterial, and then centrifuged, dispersed and dried in sequence to obtain the hollow mesoporous silica nanomaterial loaded with astaxanthin.

[0021] The present invention provides a method for preparing a hollow mesoporous silica nanomaterial, comprising the following steps:

[0022] (1) mixing CTAB, tetraethyl orthosilicate, ammonia water, ethanol and water and performing a hydrolysis reaction to obtain a gel mixture; (2) mixing the gel mixture obtained in step (1) and water and performing a condensation reaction, and then adding hydrochloric acid to perform a template removal treatment to obtain hollow mesoporous silica spheres; (3) heat-treating the hollow mesoporous silica spheres obtained in step (2) to obtain hollow mesoporous silica nanomaterials. The present invention adopts a sol-gel method to prepare solid mesoporous silica spheres, with CTAB as a template, ammonia water as a catalyst, ethanol and water as solvents, to form an ethanol-ammonia-water mixed system, in which ammonia water catalyzes the decomposition of tetraethyl orthosilicate, and is formed by the template agent to form solid mesoporous silica spheres; then the solid mesoporous silica spheres are spontaneously transformed into hollow mesoporous silica spheres through a condensation reaction, and then the template agent is removed, and finally the structure of the hollow mesoporous silica spheres is optimized by heat treatment, so that the obtained hollow mesoporous silica nanomaterial HMSS has the characteristics of large specific surface area, low density and adjustable internal cavity size, and at the same time, the mesopores on the silica shell layer provide a large material inlet and outlet channel, the thickness of the silica shell layer is adjustable, and the surface can be modified, so that it shows unique development potential in the fields of catalysis, adsorption, biosensing, drug carriers and sustained release. The results of the embodiment show that the hollow mesoporous silica nanomaterial prepared by the preparation method provided by the present invention has uniform size and shape, has a clear cavity structure, and a specific surface area of ​​800-900m 2 / g, with an average pore size of 2-50nm; hollow mesoporous silica nanomaterials can be used to load astaxanthin, and after loading, it is easily absorbed by the cumbria clams; after long-term feeding of HMSS-ASX solution to the MSS-ASX group, the changes in the shell color and pearls of the cumbria clams were more obvious than those in the control group and the ASX group, indicating that HMSS-ASX effectively enhanced the pigmentation effect of astaxanthin. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a SEM image of the hollow mesoporous silica nanomaterial prepared in Example 1;

[0024] Figure 2 This is the TEM image of the hollow mesoporous silica nanomaterial prepared in Example 1.

[0025] Figure 3A comparison chart of the fluorescence characteristics of HMSS in step I, HMSS-CY7 fluorescent particles in step IV, and CY7 solution in step III of Application Example 4;

[0026] Figure 4 For Application Example 4, the HMSS-CY7 mixed solution was fed to the cuming oyster, and the fluorescence images of the visceral organs of the cuming oyster were obtained at different times;

[0027] Figure 5 The effects of the control group, HMSS group and HMSS-ASX group in Application Example 5 on the growth of one-year-old juvenile clams;

[0028] Figure 6 The effects of the control group, ASX group and HMSS-ASX group in Application Example 5 on the growth of 3-year-old pearl oysters;

[0029] Figure 7 The changes in the activities of antioxidant enzymes (TP, SOD, CAT, T-AOC, GSH, MDA) and immune indexes (NO, ACP, AKP) in the mantle tissue of the 3-year-old pearl oysters of Application Example 5 at different time periods (0, 10, 20, 50 days) in the control group, HMSS group and HMSS-ASX group;

[0030] Figure 8 The blood of the 3-year-old pearl oysters in Application Example 5 was used to analyze the changes in the activities of antioxidant enzymes (TP, SOD, CAT, T-AOC, GSH) and immune indexes (NO, ACP, AKP) in the control group, HMSS group and HMSS-ASX group at different time periods (0, 10, 20, 50 days);

[0031] Fig. 9 The changes in the activities of antioxidant enzymes (TP, SOD, CAT, T-AOC, GSH) and immune indexes (NO, ACP, AKP) in the gill tissues of the 3-year-old pearl oysters of Application Example 5 at different time periods (0, 10, 20, 50 days) in the control group, HMSS group and HMSS-ASX group;

[0032] Fig.10 The changes in the activities of antioxidant enzymes (TP, SOD, CAT, T-AOC, GSH) and immune indexes (NO, ACP, AKP) of the visceral tissues of the 3-year-old pearl oysters of Application Example 5 at different time periods (0, 10, 20, 50 days) in the control group, HMSS group and HMSS-ASX group;

[0033] Fig.11The changes in the activities of antioxidant enzymes (TP, SOD, CAT, T-AOC, GSH) and immune indexes (NO, ACP, AKP) in the axe-foot tissue of the 3-year-old pearl oysters of Application Example 5 at different time periods (0, 10, 20, 50 days) in the control group, HMSS group and HMSS-ASX group;

[0034] Fig.12 The changes in the activities of antioxidant enzymes (TP, SOD, CAT, T-AOC, GSH, MDA) and immune indexes (NO, ACP, AKP) in the mantle tissue of the 3-year-old pearl oysters of Application Example 5 at different time periods (0, 10, 20, 50 days) in the control group, HMSS group and HMSS-ASX group;

[0035] Fig.13 The blood of the 3-year-old pearl oysters in Application Example 5 was used to analyze the changes in the activities of antioxidant enzymes (TP, SOD, CAT, T-AOC, GSH) and immune indexes (NO, ACP, AKP) in the control group, HMSS group and HMSS-ASX group at different time periods (0, 10, 20, 50 days);

[0036] Fig.14 The changes in the activities of antioxidant enzymes (TP, SOD, CAT, T-AOC, GSH) and immune indexes (NO, ACP, AKP) in the gill tissues of the 3-year-old pearl oysters of Application Example 5 at different time periods (0, 10, 20, 50 days) in the control group, HMSS group and HMSS-ASX group;

[0037] Fig.15 The changes in the activities of antioxidant enzymes (TP, SOD, CAT, T-AOC, GSH) and immune indexes (NO, ACP, AKP) of the visceral tissues of the 3-year-old pearl oysters of Application Example 5 at different time periods (0, 10, 20, 50 days) in the control group, HMSS group and HMSS-ASX group;

[0038] Fig.16 The changes in the activities of antioxidant enzymes (TP, SOD, CAT, T-AOC, GSH) and immune indexes (NO, ACP, AKP) in the axe-foot tissue of the 3-year-old pearl oysters of Application Example 5 at different time periods (0, 10, 20, 50 days) in the control group, HMSS group and HMSS-ASX group;

[0039] Fig.17 This is a real-life comparison of the shell color and pearl color of the cuminghai clams of the control group, ASX group, and HMSS-ASX group of Application Example 6. DETAILED DESCRIPTION

[0040] The present invention provides a method for preparing a hollow mesoporous silica nanomaterial, comprising the following steps:

[0041] (1) mixing CTAB, tetraethyl orthosilicate, ammonia water, ethanol and water and performing a hydrolysis reaction to obtain a gel-like mixture;

[0042] (2) mixing the gel mixture obtained in step (1) with water to carry out a condensation reaction, and then adding hydrochloric acid to remove the template to obtain hollow mesoporous silica spheres;

[0043] (3) heat-treating the hollow mesoporous silicon spheres obtained in step (2) to obtain hollow mesoporous silica nanomaterials.

[0044] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known to those skilled in the art.

[0045] The present invention mixes CTAB, tetraethyl orthosilicate, ammonia water, ethanol and water and then performs a hydrolysis reaction to obtain a gel-like mixture. The present invention adopts a sol-gel method to prepare solid mesoporous silicon spheres, wherein CTAB is a template, ammonia water is a catalyst, and ethanol and water are solvents to form a mixed system of ethanol-ammonia water-water. In the mixed system, ammonia water catalyzes the decomposition of tetraethyl orthosilicate and is formed by the template to form solid mesoporous silicon spheres.

[0046] In the present invention, the ratio of the mass of CTAB (hexadecyltrimethylammonium bromide), the volume of tetraethyl orthosilicate, the volume of ammonia water, the volume of ethanol and the volume of water is preferably (0.2-0.4) g: (1.4-2.7) mL: (0.3-0.7) mL: (32-63) mL: (67-133) mL, and more preferably 0.3 g: 2 mL: 0.5 mL: 47 mL: 100 mL. In the present invention, the water is preferably deionized water; the ammonia water is preferably concentrated ammonia water; the mass concentration of the ammonia water is preferably 25-28%, and more preferably 28%. By controlling the amount of each component, the present invention can synthesize solid mesoporous silica spheres from tetraethyl orthosilicate and form a gel-like mixture at the same time.

[0047] In the present invention, the CTAB, tetraethyl orthosilicate, ammonia water, ethanol and water are preferably mixed in the following manner: ammonia water, ethanol and water are first mixed to obtain a mixed solution, and then CTAB is added to the mixed solution, and tetraethyl orthosilicate is added after heating. In the present invention, the heating temperature is preferably 30 to 40° C., more preferably 35° C. By mixing in the above manner, the raw materials can be mixed more evenly, so that tetraethyl orthosilicate can synthesize solid mesoporous silica spheres.

[0048] In the present invention, the temperature of the hydrolysis reaction is preferably 30-40°C, more preferably 35°C; the time of the hydrolysis reaction is preferably 20-30h, more preferably 24h; the hydrolysis reaction is preferably carried out under stirring conditions; the stirring method is preferably magnetic stirring. The present invention can promote the hydrolysis of tetraethyl orthosilicate by controlling the temperature and time.

[0049] In the present invention, the gel-like mixture is preferably a white transparent gel-like mixture.

[0050] After obtaining the gelatinous mixture, the present invention mixes the gelatinous mixture with water to carry out a condensation reaction, and then adds hydrochloric acid to carry out a template removal treatment to obtain hollow mesoporous silica spheres.

[0051] In the present invention, the water is preferably deionized water; the volume ratio of the ethanol to water is preferably (40-50): (400-500). As an embodiment of the present invention, the volume ratio of the ethanol to water can be (45-48): (450-490), or 47:480.

[0052] In the present invention, the temperature of the condensation reaction is preferably 50-80°C; the time of the condensation reaction is preferably 1-3 hours. The present invention can spontaneously transform solid mesoporous silicon spheres into hollow mesoporous silicon spheres by controlling the temperature and time of the condensation reaction. As an embodiment of the present invention, the temperature of the condensation reaction can be 60-70°C; the time of the condensation reaction can be 2 hours.

[0053] After the mixing is completed, the present invention preferably washes the product of the condensation reaction alternately with ethanol and deionized water in sequence. In the present invention, the number of ethanol washings is preferably 3 to 5 times; the number of deionized water washings is preferably 3 to 5 times. The present invention can remove soluble impurities in the product by washing, which is convenient for subsequent template removal. As an embodiment of the present invention, the number of ethanol washings can be 4 times; the number of deionized water washings can be 4 times.

[0054] In the present invention, the hydrochloric acid is preferably prepared by mixing concentrated hydrochloric acid and water. In the present invention, the mass concentration of the concentrated hydrochloric acid is preferably 36-38%; and the volume of the concentrated hydrochloric acid is preferably 0.2% of the volume of the hydrochloric acid.

[0055] In the present invention, the volume ratio of hydrochloric acid, ethanol and water is preferably (200-300): (40-50): (400-500). The present invention can remove the template CTAB by adding hydrochloric acid; by controlling the concentration and amount of hydrochloric acid, the complete removal of CTAB can be ensured. As an embodiment of the present invention, the volume ratio of hydrochloric acid, ethanol and water can be (240-260): (45-48): (450-490), and can also be 240:47:480.

[0056] In the present invention, the temperature of the template removal treatment is preferably 50 to 80°C; the time of the template removal treatment is preferably 10 to 15 hours; and the template removal treatment is preferably carried out under stirring conditions. The present invention can further improve the removal efficiency of CTAB by controlling the temperature and time. As an embodiment of the present invention, the temperature of the template removal treatment can be 60 to 70°C; the time of the template removal treatment can be 12 to 14 hours. The present invention does not have any special limitation on the rotation speed of the stirring, which can be determined according to the technical common sense of those skilled in the art and ensure that the solution does not splash.

[0057] In the present invention, the product after template removal treatment is preferably washed, centrifuged and dried in sequence.

[0058] The present invention has no particular limitation on the specific operation and the number of times of washing, and washing with deionized water or ethanol can be used as long as the impurities can be removed.

[0059] The present invention has no particular limitation on the specific operation of the centrifugation, as long as it can separate the solid and the liquid.

[0060] In the present invention, the drying is preferably carried out in a blast drying oven; the drying temperature is preferably 70 to 80° C.; and the drying time is preferably 8 to 10 hours. The present invention can remove residual liquid through drying treatment to obtain dry hollow mesoporous silica spheres.

[0061] After obtaining the hollow mesoporous silicon spheres, the present invention performs heat treatment on the hollow mesoporous silicon spheres to obtain hollow mesoporous silicon dioxide nanomaterials.

[0062] In the present invention, the temperature of the heat treatment is preferably 500-600°C; the time of the heat treatment is preferably 4-10h; the heating rate to the heat treatment temperature is preferably 0.5-2°C / min; the heat treatment is preferably carried out in a high-pressure tube furnace. The present invention heat treats the hollow mesoporous silica spheres to make the obtained hollow mesoporous silica nanomaterial HMSS have the characteristics of large specific surface area, low density, adjustable internal cavity size, mesopores on the silica shell providing material inlet and outlet channels, adjustable thickness and surface modifiable, so that it shows unique development potential in the fields of catalysis, adsorption, biosensing, drug carriers and sustained release. As an embodiment of the present invention, the temperature of the heat treatment can be 550-580°C; the time of the heat treatment can be 5-8h; the heating rate to the heat treatment temperature can be 1-1.5°C / min.

[0063] In the present invention, the specific surface area of ​​the hollow mesoporous silica nanomaterial is preferably 800 to 900 m 2 / g; the average pore size of the hollow mesoporous silica nanomaterial is preferably 2 to 50 nm.

[0064] The present invention adopts a sol-gel method to prepare solid mesoporous silica spheres, using CTAB as a template, ammonia water as a catalyst, ethanol and water as solvents to form an ethanol-ammonia water-water mixed system, in which ammonia water catalyzes the decomposition of tetraethyl orthosilicate, and is formed by the template agent to form solid mesoporous silica spheres; then the solid mesoporous silica spheres are spontaneously transformed into hollow mesoporous silica spheres through a condensation reaction, and then the template agent is removed, and finally the structure of the hollow mesoporous silica spheres is optimized through heat treatment, so that the obtained hollow mesoporous silica nanomaterial HMSS has the characteristics of large specific surface area, low density, adjustable internal cavity size, mesopores on the silica shell layer providing material inlet and outlet channels, adjustable thickness, and surface modifiable, so that it shows unique development potential in the fields of catalysis, adsorption, biosensing, drug carriers and sustained release.

[0065] The present invention also provides a hollow mesoporous silica nanomaterial prepared by the preparation method described in the above technical solution.

[0066] In the present invention, the hollow mesoporous silica nanomaterial has both a mesoporous shell structure and a cavity structure; the specific surface area of ​​the hollow mesoporous silica nanomaterial is preferably 800 to 900 m 2 / g; the average pore size of the hollow mesoporous silica nanomaterial is preferably 2 to 50 nm.

[0067] The hollow mesoporous silica nanomaterial provided by the present invention is uniform in size and shape, has an obvious cavity structure, and has a large specific surface area. It has a good adsorption effect on astaxanthin, and the average pore size is sufficient to accommodate astaxanthin molecules with a size of 0.86 nm, thereby achieving the loading of astaxanthin.

[0068] The hollow mesoporous silica nanomaterial provided by the present invention has the characteristics of large specific surface area and low density, and also has the characteristics of adjustable internal cavity size, mesopores on the silica shell providing material inlet and outlet channels, adjustable thickness and modifiable surface.

[0069] The present invention also provides the use of the hollow mesoporous silica nanomaterial described in the above technical solution in loading astaxanthin.

[0070] In the present invention, the application preferably comprises the following steps:

[0071] 1) mixing astaxanthin and acetone to obtain an astaxanthin buffer solution;

[0072] 2) The astaxanthin buffer solution obtained in step 1) is mixed with the hollow mesoporous silica nanomaterial, and then centrifuged, dispersed and dried in sequence to obtain the hollow mesoporous silica nanomaterial loaded with astaxanthin.

[0073] The present invention preferably mixes astaxanthin and acetone to obtain an astaxanthin buffer solution.

[0074] In the present invention, the concentration of the astaxanthin buffer solution is preferably 10 to 35 μg / mL. The present invention is beneficial to the adsorption of astaxanthin in the buffer solution by the hollow mesoporous silica nanomaterial by controlling the concentration of the astaxanthin buffer solution. As an embodiment of the present invention, the concentration of the astaxanthin buffer solution can be 10 μg / mL, 15 μg / mL, 20 μg / mL, 25 μg / mL, 30 μg / mL or 35 μg / mL.

[0075] After obtaining the astaxanthin buffer solution, the present invention preferably mixes the astaxanthin buffer solution with a hollow mesoporous silica nanomaterial, and then sequentially performs centrifugation, dispersion and drying to obtain a hollow mesoporous silica nanomaterial loaded with astaxanthin.

[0076] In the present invention, the ratio of the volume of the astaxanthin buffer solution to the mass of the hollow mesoporous silica nanomaterial is preferably (10-30) mL: (10-30) mg. The present invention can ensure that the astaxanthin is fully loaded by controlling the dosage relationship between the two. As an embodiment of the present invention, the ratio of the volume of the astaxanthin buffer solution to the mass of the hollow mesoporous silica nanomaterial can be (15-25) mL: (15-25) mg, or can be 20 mL: 20 mg.

[0077] In the present invention, the mixing temperature is preferably 25-27°C; the mixing time is preferably 1-3h; the mixing is preferably carried out under light-proof and stirring conditions; the stirring rate is preferably 200-500rpm. The present invention can avoid the degradation of astaxanthin by controlling the parameters during mixing. As an embodiment of the present invention, the mixing temperature can be 26-27°C; the mixing time can be 2h; the stirring rate is preferably 300-400rpm.

[0078] The present invention has no particular limitation on the specific operation of the centrifugation, as long as it can separate the solid and the liquid. As an embodiment of the present invention, the centrifugation can be a high-speed low-temperature centrifugation technique. The present invention has no particular limitation on the specific temperature and centrifugation rate of the high-speed low-temperature centrifugation technique, which can be determined according to the technical common sense of those skilled in the art.

[0079] In the present invention, the dispersion method is preferably to add deionized water for dispersion. The present invention has no particular limitation on the specific amount of deionized water, as long as it can disperse the centrifuged product. The present invention can avoid the agglomeration of hollow mesoporous silica nanomaterials by adding deionized water.

[0080] In the present invention, the drying temperature is preferably -110 to -100°C; the drying time is preferably 20 to 30 hours; and the drying is preferably carried out in a freeze dryer. The present invention can avoid the degradation of astaxanthin by freeze drying. As an embodiment of the present invention, the drying temperature can be -105°C; and the drying time can be 24 hours.

[0081] When the hollow mesoporous silica nanomaterial provided by the present invention is used to load astaxanthin, the two generate dynamic forces by means of a physical adsorption method, including van der Waals interaction, hydrogen bonding, and electrostatic interaction, so that astaxanthin is stably coated on the surface and internal space of the hollow mesoporous silica nanomaterial, thereby improving the stability and biological activity of astaxanthin; at the same time, the loading process of astaxanthin by the hollow mesoporous silica nanomaterial is relatively simple, without the need to add any chemical additives, nor the need for extreme environments such as high temperature and high pressure, and does not involve a long chemical reaction process, so it will not change the color and chemical structure of astaxanthin, and its operation is simple and efficient.

[0082] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0083] Example 1

[0084] A method for preparing a hollow mesoporous silica nanomaterial comprises the following steps:

[0085] (1) 0.5 mL of aqueous ammonia (mass concentration of 25%), 47 mL of ethanol and 100 mL of deionized water were mixed to obtain a mixed solution, and then 0.3 g of CTAB was added to the mixed solution, and 2 mL of tetraethyl orthosilicate was added after heating at 35° C. with a magnetic stirrer, and a hydrolysis reaction was carried out under magnetic stirring to obtain a gel mixture; the hydrolysis reaction temperature was 35° C., and the hydrolysis reaction time was 24 h;

[0086] (2) mixing the gel mixture obtained in step (1) with 480 mL of deionized water to carry out a condensation reaction, then washing with ethanol and deionized water alternately for 4 times, then adding 240 mL of 2 mol / L hydrochloric acid to carry out template removal treatment under stirring conditions, and finally washing, centrifuging and drying in sequence to obtain hollow mesoporous silica spheres; the condensation reaction temperature is 70° C., and the condensation reaction time is 2 h; the template removal treatment temperature is 60° C., and the template removal treatment time is 12 h; the drying is carried out in a blast drying oven, the drying temperature is 70° C., and the drying time is 8 h;

[0087] (3) The hollow mesoporous silica spheres obtained in step (2) are heat-treated in a high-pressure tube furnace to obtain hollow mesoporous silica nanomaterials, labeled as HMSS; the heat treatment temperature is 550°C, the heat treatment time is 5h, and the heating rate to the heat treatment temperature is 1°C / min.

[0088] The hollow mesoporous silica nanomaterial prepared in Example 1 was observed using a scanning electron microscope. The obtained SEM image is as follows: Figure 1 The hollow mesoporous silica nanomaterial prepared in Example 1 was observed using a transmission electron microscope, and the TEM image obtained was as shown in FIG. Figure 2 As shown. Figure 1 and Figure 2 It can be seen that the hollow mesoporous silica nanomaterial prepared in Example 1 of the present invention is uniform in size and shape and has an obvious cavity structure.

[0089] The hollow mesoporous silica nanomaterial prepared in Example 1 was analyzed using a specific surface area and pore size analyzer (BET), and the results obtained were: the specific surface area of ​​the hollow mesoporous silica nanomaterial was 861.7 m 2 / g, and the average pore size is 2.51nm, which is large enough to accommodate astaxanthin molecules with a size of 0.86nm, providing basic support for loading astaxanthin.

[0090] Application Example 1

[0091] The method for loading astaxanthin using the hollow mesoporous silica nanomaterial prepared in Example 1 is:

[0092] 1) mixing astaxanthin and acetone to obtain an astaxanthin buffer solution; the concentration of the astaxanthin buffer solution is 10 μg / mL;

[0093] 2) Under light-proof conditions, 20 mL of the astaxanthin buffer solution obtained in step 1) and 20 mg of the hollow mesoporous silica nanomaterial were stirred and mixed at a rate of 300 rpm at 27 ° C for 2 h, and then high-speed low-temperature centrifugation was performed to obtain a supernatant and solid particles, and then 0.5 mL of deionized water was added to the solid particles for dispersion, and finally freeze-dried at -105 ° C in a freeze dryer for 24 h to obtain a hollow mesoporous silica nanomaterial loaded with astaxanthin, which was labeled as HMSS-ASX.

[0094] Application Example 2

[0095] In step 1), the concentration of the astaxanthin buffer solution is 20 μg / mL, and other conditions are the same as those in Application Example 1, which is labeled as HMSS-ASX2.

[0096] Application Example 3

[0097] The concentration of the astaxanthin buffer solution in step 1) is 35 μg / mL, and other conditions are the same as those in Application Example 1, which is labeled as HMSS-ASX3.

[0098] The adsorption of astaxanthin by the empty mesoporous silica nanomaterials was calculated, wherein the calculation formula of the loaded astaxanthin concentration was shown in Formula I; and the cumulative loading rate was shown in Formula II;

[0099] Loaded astaxanthin concentration (LC, μg / mL) = m0-m1 Formula I;

[0100] Cumulative load factor (CLE,%) = (m0-m1) / m0×100% Formula II;

[0101] In Formula I and Formula II, m0 is the concentration of astaxanthin buffer solution, and m1 is the concentration of astaxanthin in the supernatant.

[0102] In Application Example 1, the cumulative loading rate of HMSS for 10 μg / mL astaxanthin solution is 20.3%, and the corresponding loading amount reaches 2.00 μg / mL; in Application Example 2, the cumulative loading rate of HMSS for 20 μg / mL astaxanthin solution is 22.5%, and the corresponding loading amount reaches 4.50 μg / mL; in Application Example 3, the cumulative loading rate of HMSS for 35 μg / mL astaxanthin solution is 27.0%, and the corresponding loading amount reaches 9.61 μg / mL.

[0103] Application Example 4

[0104] The fluorescent labeling method was used to analyze the carrying path of HMSS astaxanthin. The specific steps are as follows:

[0105] I. Ultrasonic mixing of 1 mL of APTES and 20 mL of anhydrous ethanol was performed, and then 50 mg of HMSS was added. The mixture was sealed and light-proof and stirred at 88°C for 24 h. The mixture was then washed three times by centrifugation with anhydrous ethanol, and then vacuum-freeze-dried for 24 h to obtain HMSS-NH2 particles.

[0106] II. Dissolve 20 mg of the HMSS-NH2 particles obtained in step I in 10 mL of phosphate buffered saline (1×PBS, pH=7.4), and disperse them uniformly by ultrasonication for 30 min to obtain a HMSS-NH2 solution;

[0107] III. Dissolve 2 mg of CY7 in 2.7 mL of deionized water, then add 0.3 mL of acetone to obtain a CY7 solution;

[0108] IV. Mix the CY7 solution obtained in step III and the HMSS-NH2 solution obtained in step II at room temperature, and stir in the dark for 24 hours. Then, wash the product by centrifugation three times with anhydrous ethanol. Finally, freeze-dry it in a freeze dryer at -105°C for 24 hours under vacuum and in the dark to obtain HMSS-CY7 fluorescent particles.

[0109] V. Mix 10 mg of the HMSS-CY7 fluorescent particles obtained in step IV with 5 mL of deionized water to obtain a HMSS-CY7 mixed solution. Take 8 groups of triangular fan clams, and then feed 7 groups of triangular fan clams with 5 mL of the HMSS-CY7 mixed solution, and leave one group unfed. Then use a small animal living imager (IVIS Ani View 100, BLT) to detect the fluorescence signals of the main organs of the triangular fan clams (the organs are taken out and placed in the imager for detection) after 0 h, 2 h, 8 h, 12 h, 24 h, 36 h, 48 h and 60 h, respectively, under the conditions of an excitation light wavelength of 740 nm and an emission light wavelength of 820 nm.

[0110] The fluorescence characteristics of HMSS in step I, HMSS-CY7 fluorescent particles in step IV, and CY7 solution in step III were analyzed by a fluorescence imaging system. The results are as follows: Figure 3 As shown. Figure 3It can be seen that the hollow mesoporous silica nanomaterial provided by the present invention has no color under a microscope, that is, no fluorescence characteristics. The CY7 solution exhibits bright red fluorescence under the excitation of green light, while the HMSS-CY7 fluorescent particles emit red fluorescence under the excitation of green light, and the background is black, indicating that the CY7 fluorescent dye can be connected to HMSS through a covalent bond, so that the distribution of HMSS in the organism can be detected by the fluorescent labeling method.

[0111] The fluorescence signals of the main organs of the cumulus clams were detected by an imaging device at 0h, 2h, 8h, 12h, 24h, 36h, 48h and 60h respectively. The results are as follows: Figure 4 As shown. Figure 4 It can be seen that after the HMSS-CY7 mixed solution was fed to the cumbria mussel, the fluorescence images of the cumbria mussel's internal organs changed significantly at different times. The fluorescence signals mainly appeared in the mantle, gills and visceral tissues of the cumbria mussel. The fluorescently labeled HMSS nanoparticles were gradually enriched within 0-12 hours after feeding through the filter feeding action of the cumbria mussel. At 12 hours, the enrichment amount was the largest and the fluorescence intensity was the strongest. After more than 12 hours, the content of HMSS nanoparticles in the cumbria mussel became less and less, and finally were metabolized out of the body.

[0112] Application Example 5

[0113] The effect of HMSS-ASX prepared in Application Example 1 on the growth index of Hyriopsis cumingii was tested by the following method:

[0114] (1) One-year-old juvenile clams (Hyriopsis cumingii) were randomly divided into a control group, a HMSS group, and a HMSS-ASX group, with 15 juvenile clams in each group, denoted as n1;

[0115] (2) The 3-year-old pearl oysters (Hyriopsis cumingii) were randomly divided into a control group, an ASX group, and a HMSS-ASX group, with 10 individuals in each group, recorded as n2;

[0116] (3) Each group was fed with Chlorella solution twice a day. The HMSS group was also fed with 20 mL of 1 mg / mL HMSS material solution, the ASX group was also fed with 20 mL of 35 μg / mL astaxanthin solution, and the HMSS-ASX group was also fed with 20 mL of 1 mg / mL HMSS-ASX solution.

[0117] Analysis of the impact of growth indicators: The growth indicators of 1-year-old juvenile clams and 3-year-old pearl clams were analyzed in each group on the 0th, 10th, 20th and 50th days, specifically: shell length growth (SLG), shell width growth (SWG), body weight growth (WG), shell length specific growth rate (SGRSL), shell width specific growth rate (SGRSW) and body weight specific growth rate (SGRW).

[0118] Analysis of tissue antioxidant and immune capabilities: For one-year-old juvenile clams, blood was collected on the 0th, 10th, 20th and 50th days respectively. For three-year-old pearl clams, blood, mantle, gills, visceral mass and axe-foot tissues were collected on the 50th day respectively. The tissue weights were accurately recorded and stored at -30℃. The antioxidant enzyme activities and immune activities of each tissue sample were tested.

[0119] Effects of astaxanthin on the growth of 1-year-old juvenile clams Figure 5 As shown in Figure 2, the effect of astaxanthin on the growth of 3-year-old pearl oysters is as follows Figure 6 shown. Figure 5 and Figure 6 Data are expressed as mean ± SD, and independent sample t test was used to compare the three groups. Each index and each tissue were repeated three times (n = 3), *P < 0.05, **P < 0.01. Figure 5 It can be seen that at 50 days, the growth rate of shell length, shell width and weight of the one-year-old juvenile clams in the HMSS-ASX group fed with HMSS-ASX solution were significantly higher than those in the control group and the HMSS group, and the growth rate was also significantly higher than the latter two groups; Figure 6 It can be seen that at 50 days, the shell length growth rate, shell width growth rate and weight growth of the 3-year-old pearl oysters in the HMSS-ASX group fed with the HMSS-ASX solution were significantly higher than those of the control group and the ASX group, and the growth rate was also significantly higher than the latter two, indicating that the HMSS-ASX provided by the present invention can make astaxanthin more easily absorbed by the cumbria clams.

[0120] Effects of astaxanthin on antioxidant enzyme activities and immune activity in one-year-old clams Figures 7 to 11 As shown, Figures 7 to 11 Data are expressed as mean ± standard deviation (n = 3), *P < 0.05, **P < 0.01, ***P < 0.001. Figure 7 The changes in the activities of antioxidant enzymes (TP, SOD, CAT, T-AOC, GSH, MDA) and immune indexes (NO, ACP, AKP) in the mantle tissue of one-year-old juvenile clams in the control group, HMSS group and HMSS-ASX group at different time periods (0, 10, 20, 50 days); Figure 8 The changes in the activities of antioxidant enzymes (TP, SOD, CAT, T-AOC, GSH) and immune indexes (NO, ACP, AKP) in the blood of one-year-old juvenile clams at different time periods (0, 10, 20, 50 days) in the control group, HMSS group, and HMSS-ASX group; Fig. 9The changes in the activities of antioxidant enzymes (TP, SOD, CAT, T-AOC, GSH) and immune indexes (NO, ACP, AKP) in the gill tissues of one-year-old juvenile clams at different time periods (0, 10, 20, 50 days) in the control group, HMSS group, and HMSS-ASX group; Fig.10 The changes in the activities of antioxidant enzymes (TP, SOD, CAT, T-AOC, GSH) and immune indexes (NO, ACP, AKP) in the visceral tissues of one-year-old juvenile clams in the control group, HMSS group and HMSS-ASX group at different time periods (0, 10, 20, 50 days); Fig.11 The changes in the activities of antioxidant enzymes (TP, SOD, CAT, T-AOC, GSH) and immune indexes (NO, ACP, AKP) in the axe-foot tissues of one-year-old juvenile clams at different time periods (0, 10, 20, 50 days) in the control group, HMSS group, and HMSS-ASX group. Figures 7 to 11 It can be seen that after feeding the HMSS-ASX provided by the present invention, the antioxidant enzyme activity and immune index activity of one-year-old clams at 50 days were significantly improved, indicating that the HMSS-ASX provided by the present invention can improve the utilization rate of astaxanthin.

[0121] Effects of astaxanthin on antioxidant enzyme activities and immune activity in 3-year-old pearl oysters Figures 12 to 16 As shown, Figures 12 to 16 Data are expressed as mean ± standard deviation (n = 3), *P < 0.05, **P < 0.01, ***P < 0.001. Fig.12 The changes in the activities of antioxidant enzymes (TP, SOD, CAT, T-AOC, GSH, MDA) and immune indexes (NO, ACP, AKP) in the mantle tissue of 3-year-old pearl oysters in the control group, HMSS group and HMSS-ASX group at different time periods (0, 10, 20, 50 days); Fig.13 The changes in the activities of antioxidant enzymes (TP, SOD, CAT, T-AOC, GSH) and immune indexes (NO, ACP, AKP) in the blood of 3-year-old pearl oysters at different time periods (0, 10, 20, 50 days) in the control group, HMSS group and HMSS-ASX group; Fig.14 The changes in the activities of antioxidant enzymes (TP, SOD, CAT, T-AOC, GSH) and immune indexes (NO, ACP, AKP) in the gill tissues of 3-year-old pearl oysters at different time periods (0, 10, 20, 50 days) in the control group, HMSS group and HMSS-ASX group; Fig.15The changes in the activities of antioxidant enzymes (TP, SOD, CAT, T-AOC, GSH) and immune indexes (NO, ACP, AKP) in the visceral tissues of 3-year-old pearl oysters in the control group, HMSS group and HMSS-ASX group at different time periods (0, 10, 20, 50 days); Fig.16 The changes in the activities of antioxidant enzymes (TP, SOD, CAT, T-AOC, GSH) and immune indexes (NO, ACP, AKP) in the axe-foot tissue of 3-year-old pearl oysters in the control group, HMSS group and HMSS-ASX group at different time periods (0, 10, 20, 50 days). Figures 12 to 16 It can be seen that after feeding the HMSS-ASX provided by the present invention, the antioxidant enzyme activity and immune index activity of 3-year-old pearls at 50 days were significantly improved, indicating that the HMSS-ASX provided by the present invention can improve the utilization rate of astaxanthin.

[0122] Application Example 6

[0123] The effect of HMSS-ASX prepared in Application Example 1 on the shell color and pearl color of Hyriopsis cumingii was tested by the following method:

[0124] (1) The 3-year-old pearl oysters (Hyriopsis cumingii) were randomly divided into a control group, an ASX group, and a HMSS-ASX group, with 10 individuals in each group, denoted as n2;

[0125] (2) Each group was fed with Chlorella solution twice a day. The control group was fed with 20 mL of HMSS material solution, the ASX group was fed with 20 mL of 35 μg / mL astaxanthin solution, and the HMSS-ASX group was fed with 20 mL of HMSS-ASX solution.

[0126] Analysis of the impact of color indicators: Use Konica Minolta (China) CR-10Plus small colorimeter to measure the shell color and pearl color of different groups at different stages, and record the data (L*, a*, b*, dE*).

[0127] In the field of color, L* is regarded as a unit of brightness, which is used to describe the relative brightness of a specific object or environment. When L*>0 of the measured object, the color it displays tends to be white; when L*<0, the color is more black, and as the L* value decreases, the depth of the color displayed also deepens. If a*>0 of the color indicates that the color of the measured object is closer to red, while a*<0 means that the color is closer to green; for the cases of b*>0 and b*<0, it can also be inferred that the color of the measured object is closer to yellow or blue. The color difference parameter dE* can measure the degree of difference between the color of an object and the ideal white. The larger the dE* value, the stronger and richer the layering of the color of the measured object.

[0128] In the comparison of the inner shell color of the cuming oyster, the L* of the HMSS-ASX group decreased by 11.19% compared with the control group; a* shifted 346.95% to red; b* shifted 29.80% to blue; and the color richness of dE* increased by 12.84%. However, the L* of the ASX group only decreased by 8.46%; a* shifted only 122.54% to red; b* shifted only 22.67% to blue; and the color richness of dE* only increased by 8.26%.

[0129] In the comparison of pearl colors of Hyriopsis cumingii, the L* of the HMSS-ASX group decreased by 26.97% compared with the control group; a* shifted 58.27% to red; b* shifted 38.68% to blue; and the color richness of dE* increased by 35.75%. However, the L* of the ASX group only decreased by 14.28%; a* shifted only 43.77% to red; b* shifted only 20.16% to blue; and the color richness of dE* only increased by 18.27%.

[0130] The shell color and pearl color of the cuming oyster in the control group, ASX group and HMSS-ASX group are as follows Fig.17 As shown. Fig.17 It can be seen that after long-term feeding of HMSS-ASX solution, the changes in shell color and pearls of the HMSS-ASX group were more obvious than those in the control group and the ASX group, indicating that HMSS-ASX effectively enhanced the pigmentation effect of astaxanthin.

[0131] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a hollow mesoporous silica nanomaterial, comprising the following steps: (1) mixing CTAB, tetraethyl orthosilicate, ammonia water, ethanol and water and performing a hydrolysis reaction to obtain a gel-like mixture; (2) mixing the gel mixture obtained in step (1) with water to carry out a condensation reaction, and then adding hydrochloric acid to remove the template to obtain hollow mesoporous silica spheres; (3) heat-treating the hollow mesoporous silicon spheres obtained in step (2) to obtain hollow mesoporous silica nanomaterials.

2. The preparation method according to claim 1, characterized in that: In the step (1), the ratio of the mass of CTAB, the volume of tetraethyl orthosilicate, the volume of aqueous ammonia, the volume of ethanol and the volume of water is (0.1-0.5) g: (1-3) mL: (0.1-1) mL: (40-50) mL: 100 mL.

3. The preparation method according to claim 1, characterized in that: The temperature of the hydrolysis reaction in step (1) is 30 to 40° C., and the time of the hydrolysis reaction is 20 to 30 hours.

4. The preparation method according to claim 1, characterized in that: The temperature of the condensation reaction in step (2) is 50 to 80° C., and the time of the condensation reaction is 1 to 3 hours.

5. The preparation method according to claim 1, characterized in that: The temperature of the de-template treatment in step (2) is 50-80° C., and the time of the de-template treatment is 10-15 hours.

6. The preparation method according to claim 1, characterized in that: The heat treatment temperature in step (3) is 500-600° C., and the heat treatment time is 4-10 hours.

7. The preparation method according to claim 1, characterized in that: The specific surface area of ​​the hollow mesoporous silica nanomaterial in step (3) is 800 to 900 m 2 / g, the average pore size of the hollow mesoporous silica nanomaterial is 2 to 50 nm.

8. The hollow mesoporous silica nanomaterial prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the hollow mesoporous silica nanomaterial according to claim 8 in loading astaxanthin.

10. The use according to claim 9, characterized in that: The application comprises the following steps: 1) mixing astaxanthin and acetone to obtain an astaxanthin buffer solution; 2) The astaxanthin buffer solution obtained in step 1) is mixed with the hollow mesoporous silica nanomaterial, and then centrifuged, dispersed and dried in sequence to obtain the hollow mesoporous silica nanomaterial loaded with astaxanthin.